Mentoring for Identifying Operational Waste at PKU Sekapuk Hospital - Tjatur Ermitajani Judi (LP3M IAI At-Tahdzib, 2025)
The intense competition in the healthcare industry in Lamongan Regency demands that private hospitals abandon traditional governance models that trigger high levels of wasteful spending. The Pembina Kesejahteraan Umat Hospital (RS PKU) in Sekapuk faces managerial challenges where 80% of its staff have purely clinical backgrounds without modern governance skills, leading to service inefficiencies and revenue leakage. The Community Empowerment Program (CEP) aims to detect, measure, and map existing operational inefficiency nodes in the hospital’s healthcare facilities. The implementation method is carried out through technical mentoring and collaborative Focus Group Discussions (FGDs) with 25 core hospital managers, adopting the curriculum of the Asian Tiger Healthcare Camp and the Ikatan Konsultan Kesehatan Indonesia (Ikkesindo). The results of the CEP indicate a simultaneous accumulation of high-level waste across all parameters of the Seven Biggest Sources of Wasteful Spending instrument. The main root causes are detected in outpatient queues (operational inefficiencies), uncertainty in the conventional pharmaceutical supply chain, and delayed claim files (revenue leakage). This comprehensive audit successfully formulated a new governance roadmap that serves as a scientific basis for the board of directors in determining priorities for sustainable quality interventions.